Implementation of Policy in the Supervision of Illegal Cigarette Circulation in Kudus Regency: A Grindle Model Perspective - Feri Dwi Kustanto; Siti Aisyah; Asih Widi Lestari (Universitas Medan Area, 2026)
This study analyzes the implementation of the policy regarding the supervision of illegal cigarette circulation in Kudus Regency, utilizing Grindle's Implementation Model. Using a descriptive qualitative method, data were collected through in-depth interviews, observations, and document analysis. The findings reveal a significant discrepancy between the normative content of policy and the actual implementation context in the field. Specifically, the policy implementation is constrained by limited enforcement resources and economic resistance from small business actors. Although intelligence mapping has improved, the lack of a participatory approach hinders Small and Medium Enterprises (SMEs) from competing effectively. Consequently, this study recommends optimizing resource allocation and fostering cross-sector collaboration better aligned with Kudus's local economic ecosystem.